"I feel like eating rice 24 hours per day, 7 days a week": A Study of Dietary Diversity Among Asylum Seekers in Norway (OR21-06-19). (13th June 2019) - Henjum, Sigrun; Terragni, Laura
Abstract: Objectives: Poor nutrition and food insecurity is highly prevalent among asylum seekers residing in western countries. Lack of economic resources, unfamiliarity with new foods, and language barriers are some challenges that asylum seekers encounter upon resettlement. Despite the importance of an adequate diet for good health, limited knowledge, exist on food intake and dietary quality among asylum seekers. We described dietary intake and assessed dietary quality among asylum seekers at Norwegian reception centers. Methods: In 2017, a cross-sectional study in eight ordinary asylum reception centers in the South Eastern part of Norway were performed and 205 asylum seekers (131 men and 74 women) were included. Dietary intake was assessed by 24-hour dietary recall and dietary diversity score (DDS) calculated according to FAO and FANTA, 2014. In addition, field notes of the asylum seekers thoughts on dietary intake and living condition provided contextual aspects of their nutritional situation. Results: Two-third of the asylum seekers had dietary intakes with low quality; they ate from less than five food groups (low DDS). The asylum seekers ate in average two meals per day and one-third ate their first meal after noon. Meals tend to consist of food that was familiar in their country of origin. Women had significantly higher DDS than men with a higher consumption of vegetables and fruits. Asylum seekers residing in Norway for a longer time had a higher dietary diversity, than asylum seekers with a shorter stay. Most asylum seekers told about a reduced dietary intake, few meals and by the end of the month, hunger. They chose the cheapest food, food on sale or food that had expired and chose quantity over quality. The kitchen facilities at the reception centers were inadequate with limited storage place, low quality of the cooking equipment and crowded kitchen. Conclusions: The asylum seekers had a monotonous diet with few meals, in contrast to the food abundance that most Norwegian are accustomed to, revealing, the emergence of new groups and new forms of poverty and social exclusion also in rich countries with otherwise good welfare state systems. The situation appear particularly critical given Norway's commitment through the United Nations (UN) International Covenant on Economic, Social and Cultural Rights to ensure human rights such as the right to adequate food and health. Funding Sources: The study was funded by Oslo Metropolitan University, Norway.